Assessing Lake Response to Extreme Climate Change Using the Coupled MIKE SHE/MIKE 11 Model: Case Study of Lake Zazari in Greece - K. Demertzi; D. Papamichail; D. Papadimos (2022)
Papadimos D, Demertzi K, Papamichail D. Assessing Lake Response to Extreme Climate Change Using the Coupled MIKE SHE/MIKE 11 Model: Case Study of Lake Zazari in Greece. Water. 2022; 14(6):921. https://doi.org/10.3390/w14060921